El contrato de seguro y su responsabilidad civil (2006)
The present monograph is on a quite complex, exciting topic and also excellently from the academic point of view, as it is the CONTRACT OF INSURANCE AND ITS LEGAL LIABILITY and for it, it was necessary to walk along the whole Contract of Insurance, departing from its history itself, happening for the Theory of Legal liability up to coming to the Insurances of Legal liability. The first traces of what today is the Contract of Insurance are in the Code of HAMMURABI, on having been contemplated that in case of looting acts on the part of the ways salteadores, these losses would be supported by the public treasure. On having advanced the shipping activity and along with this one, commercially, the persons who somehow were intervening in them, often they took big losses as the action of the nature or as the action of the pirates, and it is as well as it arises what more looks alike for an insurance contract, when these persons decide between they insure themselves themselves, first they did it with the lives of the seamen, and on having seen the good results, this practice spread to the ships and to the goods, but it was necessary that it was passing a lot of time and with him, to reach the necessary experience to come to what is known as the activity or insurance industry.